2011
DOI: 10.3892/ijmm.2011.869
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2 inhibits the expression of stromal cell-derived factor 1α in periodontal ligament cells derived from human permanent teeth in vitro

Abstract: Although cells derived from periodontal ligament (PDL) tissue are reported to have stem cell-like activity and are speculated to play a crucial role for tissue healing and regeneration after injury or orthodontic treatment, mechanisms regulating their recruitment and activation remain unknown. Recently, stromal cell-derived factor 1α (SDF-1α) has been reported to be important for stem cell homing and recruitment to injured sites. The aim of this study was to evaluate whether fibroblast growth factor 2 (FGF-2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The underlining pathways for SDF-1 production by BMP-9 stimulation are poorly understood. It has been demonstrated that SDF-1 production is up-regulated by interleukin 17 via pathways mediated by PI3K, nuclear factor-kappaB, and activator protein-1 in human rheumatoid synovial fibroblasts (26), whereas the JNK pathway, but not the PI3K pathway, is involved in fibroblast growth factor 2-induced expression of SDF-1 in human PDL cells (8). Our data suggest, for the first time, that the PI3K/Akt pathway is involved in SDF-1 production by BMP-9 treatment in PDLFs cultured in osteogenic media.…”
Section: Discussionmentioning
confidence: 99%
“…The underlining pathways for SDF-1 production by BMP-9 stimulation are poorly understood. It has been demonstrated that SDF-1 production is up-regulated by interleukin 17 via pathways mediated by PI3K, nuclear factor-kappaB, and activator protein-1 in human rheumatoid synovial fibroblasts (26), whereas the JNK pathway, but not the PI3K pathway, is involved in fibroblast growth factor 2-induced expression of SDF-1 in human PDL cells (8). Our data suggest, for the first time, that the PI3K/Akt pathway is involved in SDF-1 production by BMP-9 treatment in PDLFs cultured in osteogenic media.…”
Section: Discussionmentioning
confidence: 99%
“…RNA (1 µg) was reversetranscribed to first-strand cDNA using a PrimeScript™ RT reagent kit (Takara Bio, Inc., Shiga, Japan) according to the manufacturer's instructions. A Thermal Cycler Dice real-time system (Takara Bio, Inc.) was used for real-time PCR (18)(19)(20). The cDNAs were amplified with SYBR ® Premix Ex Taq and specific primer pairs for fibroblast growth factor (FGF)-1 (21), FGF-2 (22), epidermal growth factor (EGF) (23), vascular endothelial growth factor (VEGF) (24,25), insulin-like growth factor-1 (IGF-1) (26), nerve growth factor (NGF), neurotrophin-3 (NT-3), brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), neuropeptide Y, β-tubulin Ⅲ, 2' ,3'-cyclic-nucleotide phosphodiesterase (CNPase), microtubule-associated protein 2 (Map2), glial fibrillary acidic protein (GFAP), nestin, glutamate receptor 1 (GluR1) (27), glutamate receptor 2 (GluR2) (27), glutamate receptor 3 (GluR3) (27), glutamate receptor 4 (GluR4) (27), N-methyl D-aspartate receptor subtype 2B (NR2B) (28) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH).…”
Section: Volume Measurement Of the Granular Cell Layer Of The Dgmentioning
confidence: 99%
“…Furthermore, individuals with periodontal disease who underwent mechanical therapy demonstrated decreased levels of this mediator 26 . In addition, CXCL12 from periodontal ligament cells was demonstrated to participate in the regeneration and homeostasis of periodontal tissues via the recruitment of stem cells 27 …”
mentioning
confidence: 99%
“…26 In addition, CXCL12 from periodontal ligament cells was demonstrated to participate in the regeneration and homeostasis of periodontal tissues via the recruitment of stem cells. 27 Concerning the participation of TLR adaptors in the production of the abovementioned cytokines by HGF and HPDLF, a previous study demonstrated that HGF CD14(+) primed with IFN-g increase production of IL-8 in response to LPS through upregulation of membrane CD14 and MyD88 mRNA expression. 28 Also, a recent report showed that IL-23 expression in primary HPDLF was abrogated by MyD88 inhibitor in IL-1b-stimulated cells.…”
mentioning
confidence: 99%